Biblioteca - barrio Jipijapa - Cisneros Pereira, Sebastián Alejandro (2020)
According to the Urban Ordering Plan carried out by the eighth semester students ARO 860 UDLA, it is determined that within the limits of the sector analyzed in the Rumipamba, Jipijapa and Iñaquito neighborhoods there is a accumulation of administrative equipment, which generates a concentration of work and commercial exchange in the center of the study area (La Carolina sector). Thanks to this, the creation of different clusters is proposed blocks for its development. By analyzing the site, we found the problems that most activities were concentrated around administrative -financial equipment, thanks to the loss of them in most activities in the sector and are a magnet to attract different commercial equipment. Therefore, with a vision to the year 2040, a development of equipment distributed in main areas is used, which according to a study, it is where the concentration of activities exists. Therefore, each cluster employs about four to five equipments of different character which activate the area where it is located. This generates a more dynamic and inclusive sector for the development of trade, economy, culture and distraction. Within the Metropolitan district of Quito, accessibility and connection to public spaces that will be creators are promoted to serve as connectors of the city. In the Jipijapa neighborhood, within the block of the Central Technical School, cluster number six is proposed which has an interactive residential and cultural character thanks to the activities of the neighborhood. In this cluster is located a cultural equipment to supply the three main educational facilities of the sector: Technical Central College, María Eufrasia College and Condamine College. This project is called a Public Library and it is intended to express the cultural character to the area for the cohesion of users in the neighborhood. According to a typological study we have the prospect of seeing a library as a place where meeting exists, the relationship and the exchange of ideas of users so that there is the knowledge and desire to discover places of social relationship where you can produce teaching through books, light and the curiosity of spaces.